If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -10x + 1 = 0 Reorder the terms: 1 + x + -10x = 0 Combine like terms: x + -10x = -9x 1 + -9x = 0 Solving 1 + -9x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -9x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -9x = 0 + -1 -9x = 0 + -1 Combine like terms: 0 + -1 = -1 -9x = -1 Divide each side by '-9'. x = 0.1111111111 Simplifying x = 0.1111111111
| -48a^3-24a^2+45a=0 | | 2x^3-x^2+8x-4=0 | | 3(a/6+3)+1/2(a+6a) | | 49c^2-84cr+36r^2=0 | | 3x-6/15x | | 36=4w+4(w+5) | | 56s^2+19st-15t^2=0 | | -1=7x+4(x-3) | | -4=-8y+2(y+4) | | -2+8s^2+3s^4=0 | | -2u+4(u-2)=-4 | | 4x(x+2)+11-4=2x+3 | | 12s^4+32s^2-8=0 | | 5(x-5)-6x=-2 | | 7/12*9/2-33/40 | | (2x^2-6x-8)/(x+1) | | 3s^4+8s^2-2=0 | | 7/x+3-5/x-3=3x/x^2-9 | | 14x^2/7x | | -13+6=m-10 | | 6v^2+3v-4=-4v^2 | | 3a^2-14a-5=0 | | 2v^2+3v-4=0 | | -13+6=m-16 | | y=-1*1 | | 7/12x9/2-33/40 | | 4/5b=120 | | 4/5b=48 | | y=-3/4*1+6 | | -0.75*-3/4x+6 | | x^2+5x-37.5=0 | | 96x^2-204x-99=0 |